Grundtvig og Kierkegaard - Toftdahl, Hellmut (Grundtvig-studier, 1991)
» Grundtvig and Kierkegaard « Otto Bertelsen: ‘ The Dialogue between Grundtvig and Kierkegaard’. Published by CA. Reitzel, Copenhagen, 1990, 129 pp.By Hellmut Toftdahl. The comparison between Kierkegaard and Grundtvig has presented a temptation for many scholars. It has led to widely different conclusions about similarities and differences. Each generation, intent upon seeking a deeper understanding of the conditions of human life and the existential message of Christianity, is likely to find that a personal attitude to the two giants in the spiritual life of the 19th century must inevitably be taken.Otto Bertelsen not only compares the ideas of the two thinkers, but also reviews them in a mutual perspective. The material provided is comprehensive and proves that the two knew each other very well. The writer also makes convincing conjectures about what they may have meant by this or that passage, and what they may have read from each other’s works. This makes for a vivid and captivating presentation and prepares for the main thesis of the book: that the dialogue between them was more extensive than has been assumed to far. In particular, the admiration felt by the young Kierkegaard for the rebellious Grundtvig, who announced that the Word of the Lord was missing in His own House, and brought himself in opposition to the Establishment with .The Rejoinder of the Church. (‘ Kirkens Genmæle’), is lucidly described so as to show how the reformer dream was a characteristic they shared. Grundtvig wanted an ‘external’ reformation by making the national church so free that even a Kierkegaard would be able to be a clergyman in it. Kierkegaard wanted an ‘internal’ reformation by presenting the Christian demand in such radical terms that everybody must desist from being counted as ‘ Witness for Truth’. If he was only allowed this ‘concession’, not one iota of change in the existing church government would be required. The writer points out that during the Church Battle Kierkegaard becomes so radical in his attacks on the Christian church that the Establishment would not have been able to survive if it had accepted the criticism.Aspects of material history are also included in the comparison. Bertelsen shows how they were both keenly aware of the suppression of the proletariat by the established church. But for both of them, social indignation was an emotion, closely linked with the charity of Christianity and a universal, liberal understanding of how miserable material conditions may deprive man of his dignity. Neither of them harboured any notions of a class revolution, but they both shared worries that a democratic, materialistic mass culture will lead the individual away from its destiny as a .divine experiment.. To Kierkegaard the cure against this would consist in an intensification of the spiritual life of the individual, while Grundtvig counted on raising the consciousness of the individual through enlightenment of the people. Bertelsen intimates that Grundtvig and Kierkegaard ‘might, together, re-vitalize the folk high school’.The book should be recommended as a quick, but thorough and honest introduction to both thinkers. It shows that the need for a personal experience of religion has not been invented by new-religious movements of the present time, but was a vital challenge for the stagnant understanding of Christianity of the previous century. It also shows that the theology of personal experience does not necessarily contest the validity of the belief that the Christian faith is essentially something unchangeable that exclusively depends on the faith in Christ. Now, towards the end of this century, which, after substituting ideologies for religion, sees ideologies crumbling, the book serves as a reminder of what we lost when we turned materialism and the social state into the Absolute.With regard to the question of maintaining one’s original identity under the external pressure from a massive socialization, which is both powerful and systematic, the dialogue between the two thinkers has acquired a renewed relevance, not just for individuals, but for whole peoples whose identity and living space is threatened by the paternalistic systematization of the present. Bertelsen’s book is a good book for Danes to bring with them into the coming Europe!